1997
DOI: 10.1088/0022-3727/30/7/002
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of N-rich a-Si - N:H films with a low electron-trapping rate

Abstract: Hydrogenated amorphous silicon nitride films with a high nitrogen content were prepared by RF plasma-enhanced chemical vapour deposition from a mixture of and at . The influence of the main operating variables on the quality of the material was examined. Characteristics and properties of the films were investigated using optical absorption, infrared spectroscopy, x-ray photo-electron spectroscopy and capacitance - voltage measurements. From infrared transmission and reflection measurements, it was found mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…A similar decrease in (D ) with the increase in the flow ratio of NH 3 /SiH 4 for the films prepared without NH 3 plasma pretreatment has also been reported by others [29,30]. The values of (D ) are observed to depend strongly on film composition and decreases with increase in the N/Si ratio.…”
Section: The Variation Of the Minimum Interface State Density (D )supporting
confidence: 86%
See 1 more Smart Citation
“…A similar decrease in (D ) with the increase in the flow ratio of NH 3 /SiH 4 for the films prepared without NH 3 plasma pretreatment has also been reported by others [29,30]. The values of (D ) are observed to depend strongly on film composition and decreases with increase in the N/Si ratio.…”
Section: The Variation Of the Minimum Interface State Density (D )supporting
confidence: 86%
“…The refractive index n decreases from 1.83 to 1.72 for the samples prepared without NH 3 plasma pretreatment while n decreases from 1.80 to 1.67 for the NH 3 plasma pretreated samples as the flow ratio of NH 3 /SiH 4 increases from 1.33 to 12.66 corresponding to silicon-rich to nitrogen-rich films. A similar decrease of refractive index n with increase in the flow ratio of NH 3 /SiH 4 for the silicon nitride films prepared without NH 3 plasma pretreatment has also been reported by others [29,30,32]. The small decrease in the refractive index for the NH 3 plasma pretreated samples may be ascribed to the slight increase in the N/Si ratio because of the nitridation.…”
Section: The Variation Of the Minimum Interface State Density (D )supporting
confidence: 83%
“…In an earlier work [19], it has been shown that the characteristics of nonstoichiometric SiN traps demonstrate a strong 0018-9383/$26.00 © 2009 IEEE decrease in the trapped charge density when films become rich in N-H bonds. It has also been shown [20], [21] that the Sirich (Si + ) SiN has higher electron trap density at relatively shallow energy levels, allowing them to get readily discharged of the electrons during E operations [22].…”
Section: Introductionmentioning
confidence: 99%
“…It increases quite rapidly to a limit value of 3.8 eV as the refractive index n decreases to value close that of Si 3 N 4 (see Figure 2, Table 1). This is mainly due to the optical properties controlled by Si-N and N-H bonds [19]. Tauc slope B could provide details on the spreading tails of valence and conduction bands.…”
Section: Optical Propertiesmentioning
confidence: 99%